-(5x-3)-3(2x-5)=

Simple and best practice solution for -(5x-3)-3(2x-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5x-3)-3(2x-5)= equation:


Simplifying
-1(5x + -3) + -3(2x + -5) = 0

Reorder the terms:
-1(-3 + 5x) + -3(2x + -5) = 0
(-3 * -1 + 5x * -1) + -3(2x + -5) = 0
(3 + -5x) + -3(2x + -5) = 0

Reorder the terms:
3 + -5x + -3(-5 + 2x) = 0
3 + -5x + (-5 * -3 + 2x * -3) = 0
3 + -5x + (15 + -6x) = 0

Reorder the terms:
3 + 15 + -5x + -6x = 0

Combine like terms: 3 + 15 = 18
18 + -5x + -6x = 0

Combine like terms: -5x + -6x = -11x
18 + -11x = 0

Solving
18 + -11x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + -11x = 0 + -18

Combine like terms: 18 + -18 = 0
0 + -11x = 0 + -18
-11x = 0 + -18

Combine like terms: 0 + -18 = -18
-11x = -18

Divide each side by '-11'.
x = 1.636363636

Simplifying
x = 1.636363636

See similar equations:

| (4x-6)/3=-2 | | 6*8*18= | | 0.49=cos(x) | | -7(3p+2)40=3(5p+6) | | 18*14*2= | | 5x+32=67 | | N/25-7=-82 | | 3x-2+7+3x-2+7=133 | | -9-5+2-8-9= | | 4x+6+x=180 | | 67y=45n+13 | | 2448/48=x | | X(x-8)=x^2+5x | | 0=40-(1.1xd) | | 49x^2-252x+224=0 | | 42-2x=125 | | 30-5=17+H | | 18(3d)+12d=4884 | | 72x^2=98 | | 3p=10-1 | | -9v-5v-v+7v+5v= | | 3n+8a=144 | | 4+x+8=-48 | | 30+15=2x+4 | | 8n+3a=144 | | 9/3.14= | | 6x-9=4x+4 | | .432=logx^2 | | .20/50 | | 3*7/6 | | (y-5)(-3y^2+6y+3)=0 | | 2x+4+3x=2x+3 |

Equations solver categories